The application of fibrous sheath subcutaneous segment in central vein recatheterization - HE Da; SU Shan-na; CHEN Fang; CHENG Li; ZHANG Huang; XIE Lan-qian; XIONG Fei (Linchuang shenzangbing zazhi)
Objective To study the feasibility and safety of application of fibrous subcutaneous segment in central vein recatheterization in selected patients.Methods A retrospective analysis was conducted for a total of 21 selected patients who underwent recatheterization through the fibrous sheath subcutaneous segment of the previous hemodialysis catheter due to catheter fall-off or other reasons,from September 2012 to June 2019,and their case data were statistically analyzed.Results A total of 21 patients were collected,including 7 males and 14 females,with an average age of(65.9±15.8) years and an average dialysis age of(27.7±24.0) months.The reasons for recatheterization included complete catheter fall-off in 11 cases,catheter-related bloodstream infection in 6 cases,long-term complete hemodialysis catheter blockage in 2 cases,and unsuccessful ectopic catheter puncture in 2 cases.Of the 21 patients,20(95.2%) achieved successful recatheterization,and 1(4.8%) underwent long-term catheterization of femoral vein after failure.In patients with successful,the X-ray examination indicated that the catheter was in good position.All the above patients’ pumping control blood flow in hemodialysis after recatheterization was equal to or greater than 250 mL/min.There were no serious complications in this group.Conclusions In situ recatheterization of hemodialysis catheter through the fibrous sheath subcutaneous segment of previous hemodialysis catheter is an economical and safe method with a high success rate and few complications,and may be used as a helpful supplement for in situ catheter replacement through a guidewire and catheter replacement through ectopic catheter puncture.